Construction Of Musyârakah Muntahiyyah Bi Al-Tamlȋk Contract In Sharia Principles-Based DSN-MUI Fatwa - Agus Putra, Panji Adam; Imaniyati, Neni Sri; Nurhasanah, Neneng; Sundari, Rini Irianti (Univeristas Islam Bandung, 2022)
The legitimacy and pros and cons of multi-contract and wa’ad mulzim-based fatwa products receive serious attention from contemporary fiqh scholars. One of the multi-contract and wa’ad mulzim-based fatwas issued by National Sharia Council-Indonesian Ulema Council (DSN-MUI) is fatwa Number 133 Year 2019 concerning Musyârakah Muntahiyyah bi al-Tamlȋk. This consists of a series of several contracts and contains the provisions of wa’ad mulzim. The purpose of the study was to examine the construction of Musyârakah Muntahiyyah bi al-Tamlȋk contract and explore sharia principles-based Musyârakah Muntahiyyah bi al-Tamlȋk contract. The method of this study was qualitative research using a normative juridical approach, and its data collection technique was library research. The result revealed that the construction of Musyârakah Muntahiyyah bi al-Tamlȋk contract in the fatwa is the allowed multi-contract, considering that the prohibition of multi-contract has legal reasons or legislature ratio. The wa’ad mulzim in the fatwa is a form of implementing the principle of benefit and providing the value of legal certainty in conducting a transaction. Thus, the fatwa of DSN-MUI regarding Musyârakah Muntahiyyah bi al-Tamlȋk is not out of sharia principles. The Implication of This Research That Ijtihad Products in the Field of Sharia Economic Law in the Form of Fatwas Can Be Used as Guidelines in Encouraging Product Innovation of Islamic Financial Institutions.